The Church music of Stanisław Moniuszko: Genre, Typology, Function, Axiology - Dąbek, Stanisław (Interdisciplinary Studies in Musicology, 2023)
Works of church music symbolically open and close Moniuszko’s creative path. Yet this species of music – by no means marginal, present during all the decades of compositional work (1839–1872) – is the least researched and not precisely ordered. This article represents the continuation of the author’s research interest in Moniuszko’s church music and covers the methodological issues relating to the genre. The four components listed in the title form the key generic ordo. Together they make up a thematically coherent complex, not previously dealt with in Polish scholarship. The aim of this article is to precisely order the composer’s church music in a scientific way. Since church music of this period is characterised by numerous literary (poetic) connections, which also applies to Moniuszko's work, scholars’ statements concerning religious themes in Polish literature and Romantic music have also been taken into account. The most general ordering of Moniuszko’s works of church music is made possible by a sort of standard musical typology (employed for music of the nineteenth and twentieth centuries), with scoring as a chief criterion. Axiology – the question of value – is the most difficult aspect of research into creative work, and it is of fundamental importance. Not all scholars take account of the philosophy of value. In the article, axiological issues are only signalled. Given the important connections between music and literature during the Romantic era (including in Moniuszko’s works of church music), the general theory of the axiology of the literary work is taken into account. The value of a work cannot be determined solely by its axiology in reception. Seen from the perspective of a ‘spiritual diary’, and also of a liturgical typology, the strands and types of piety, and literary connections, Moniuszko’s church music can be understood as ‘music of confidence and trust’, in the broader sense referring not only to individual experience, but also to collective, national experience.